Characterization of Non-coding DNA Satellites Associated with Sweepoviruses (Genus Begomovirus, Geminiviridae) – Definition of a Distinct Class of Begomovirus-Associated Satellites - Lozano, Gloria; Trenado, Helena P.; Fiallo-Olivé, Elvira; Chirinos, Dorys; Geraud-Pouey, Francis; Briddon, Rob W.; Navas-Castillo, Jesús (Frontiers in Microbiology, 2016)
Begomoviruses (family Geminiviridae) are whitefly-transmitted, plant-infecting single-stranded DNA viruses that cause crop losses throughout the warmer parts of the World. Sweepoviruses are a phylogenetically distinct group of begomoviruses that infect plants of the family Convolvulaceae, including sweet potato (Ipomoea batatas). Two classes of subviral molecules are often associated with begomoviruses, particularly in the Old World; the betasatellites and the alphasatellites. An analysis of sweet potato and Ipomoea indica samples from Spain and Merremia dissecta samples from Venezuela identified small non-coding subviral molecules in association with several distinct sweepoviruses. The sequences of 18 clones were obtained and found to be structurally similar to tomato leaf curl virus–satellite (ToLCV-sat, the first DNA satellite identified in association with a begomovirus), with a region with significant sequence identity to the conserved region of betasatellites, an A-rich sequence, a predicted stem-loop structure containing the nonanucleotide TAATATTAC, and a second predicted stem-loop. These sweepovirus-associated satellites join an increasing number of ToLCV-sat-like non-coding satellites identified recently. Although sharing some features with betasatellites, evidence is provided to suggest that the ToLCV-sat-like satellites are distinct from betasatellites and should be considered a separate class of satellites, for which the collective name deltasatellites is proposed.